Handbook of flood risk science & management - Reed, Dan (New York Magnum Publishing, 2016)
"Floods have been recurrent phenomenon in many parts of world, causing loss of lives and public property and bringing untold misery to the people, especially those in the rural areas. There is also a larger economic impact, as they derail economic activities, thus affecting growth. Flood control and management refers to all methods used to reduce or prevent the detrimental effects of flood waters. Some of the common techniques used for flood control are installation of rock berms, rock rip-raps, sandbags, maintaining normal slopes with vegetation or application of soil cements on steeper slopes and construction or expansion of drainage channels. Other methods include levees, dikes, dams, retention or detention basins. This book provides an extensive and comprehensive topics in flood risk and management."--Amazon.
Keywords: Flood control; Flood damage prevention; Risk assessment